Socialization of Women's Empowerment Through Creative Economy In The Crafts Sector - Ritonga, Zuriani; Zuhra, Fatimah; Maulana, Rizkha; Mulyadi, Mulyadi; Karimin, Karimin; Zhalikha, Zhalikha; Murniyanti, Sri (CV. Inara, 2025)
Socialization of Women's Empowerment Through Creative Economy in the Craft Sector